The influence of extended warranty policy in Malaysian culture perspective [electronic resource] : a case study in automobile - Amro Osman Widaa, 1981-; Fakulti Sains Komputer dan Sistem Maklumat (2008)
Thesis (Sarjana Sains (Teknologi Maklumat - Pembuatan)) - Universiti Teknologi Malaysia, 2008